2007 Australian Software Engineering Conference (ASWEC'07) 2007
DOI: 10.1109/aswec.2007.39
|View full text |Cite
|
Sign up to set email alerts
|

Prerequisites for Successful Architectural Knowledge Sharing

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…The need for sharing architectural knowledge was also observed in a study we conducted at a large software development organization [11]. We found that architects rely heavily on communication to work adequately and to produce high-quality results, and that many formal and informal discussions take place in the coffee room, at the hallway, or during other social events or meetings.…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…The need for sharing architectural knowledge was also observed in a study we conducted at a large software development organization [11]. We found that architects rely heavily on communication to work adequately and to produce high-quality results, and that many formal and informal discussions take place in the coffee room, at the hallway, or during other social events or meetings.…”
Section: Introductionmentioning
confidence: 73%
“…Various social [16], organizational and cultural [17], or personal factors [18] also heavily influence the success of knowledge sharing, but this is beyond the scope of this paper. More information about incentives for knowledge sharing can be found in [19], or in [11] where incentives for architectural knowledge sharing are identified.…”
Section: What To Learn From Knowledge Management?mentioning
confidence: 99%
“…11 We found that architects rely heavily on communication to work adequately and to produce high-quality results, and that many formal and informal discussions take place in the coffee room, at the hallway, or during other social events or meetings. However, despite the need for sharing architectural knowledge, software architects in practice often stick to familiar technologies such as office suites for their daily tasks.…”
mentioning
confidence: 99%
“…Farenhorst et al [24] identify difficulties that arise when sharing AK, as well as prerequisites for sharing to be successful. They define incentives for people needed to be willing to share AK, as well as the lesson that striving for completeness is infeasible.…”
Section: Related Workmentioning
confidence: 99%